Identification of transport parameters of chlorides in different soils on the basis of column studies - Pietrzak, Damian; Kania, Jarosław; Kmiecik, Ewa; Wątor, Katarzyna (Geologos, 2019)
Knowledge of transport patterns of chemicals in groundwater is essential for environmental assessment of their potential impact. In the present study, the mobility of a chloride tracer injected into three different soils was investigated, using column experiments. The column tests were performed under steady-state conditions to determine parameters of chloride migration through soils. Based on breakthrough curves, pore-water velocity, dispersion coefficient and dispersivity constant were calculated for each soil sample using CXTFIT/STANMOD software. Pore-water velocity was in the range of 0.31 cm/min for fine sand, to 0.35 cm/min for silty sand and to 0.40 cm/min for vari-grained sand. The highest values of dispersion coefficient and dispersivity constant were observed for silty sand (0.55 cm2/min and 1.55 cm, respectively), while the lowest value was found for fine sand (0.059 cm2/min and 0.19 cm, respectively). Column experiments for chlorides (conservative tracer) are a preliminary stage for further research which will be undertaken to investigate migration parameters of selected neonicotinoids (reactive tracers) through different soils.